Oxy-CO2 reforming of methane to syngas over CoOx/MgO/SA-5205 catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Fuel, 2006)
The OXY-CO2 methane reforming reaction (OCRM) has been investigated over CoOx supported on a MgO precoated highly macroporous silica-alumina catalyst carrier (SA-5205) at different reaction temperatures (700-900 degrees C), O-2/CH4 ratios (0.3-0.45) and space velocites (20,000-100,000cc/g/h). The reaction temperature had a profound influence on the OCRM performance over the CoO/MgO/SA-5205 catalyst; the methane conversion, CO2 conversion and H-2 selectivity increased while the H-2/CO ratio decreased markedly with increasing reaction temperature. While the O-2/CH4 ratio did not strongly affect the CH4 and CO2 conversion and H-2 selectivity, it had an intense influence on the H-2/CO ratio. The CH4 and CO2 conversion and the H-2 selectivity decreased while the H-2/CO increased with increasing space velocity. The O-2/CH4 ratio and the reaction temperature could be used to manipulate the heat of the reaction for the OCRM process. Depending on the O-2/CH4 ratio and temperature the OCRM process could be operated in a mildly exothermic, thermal neutral or mildly endothermic mode. The OCRM reaction became almost thermoneutral at an OCRM reaction temperature of 850 degrees C, O-2/CH4 ratio of 0.45 and space velocity of 46,000 cc/g/h. The CH4 conversion and H-2 selectivity over the CoO/MgO/SA-5205 catalyst corresponding to thermoneutral conditions were excellent: 95% and 97%, respectively with a H-2/CO ratio of 1.8. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: methane; oxy-CO2 reforming; Syngas

Partial oxidation of methane to syngas with or without simultaneous steam or CO2 reforming over a high-temperature stable-NiCoMgCeOx supported on zirconia-hafnia catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Applied Catalysis A-General, 2006)
A NiCoMgCeOx (Ni/Co/Mg/Ce: 1:0.2:1.2:1.2)/zirconia-hafnia catalyst with unusually high thermal stability has been investigated for syngas generation via a process that includes the catalytic partial oxidation of methane (CPOM), the oxidative steam reforming of methane (OSRM) and the oxidative CO2 reforming of methane (OCRM). The catalyst calcined at 1400 degrees C (for 4 h) showed excellent activity/selectivity for the CPOM, OSRM and the OCRM reactions; furthermore no catalyst deactivation was observed for a period of 20 h. For the CPOM process, the selectivity for H-2 was > 95% at reaction temperatures > 650 degrees C however temperatures above 800 degrees C were required to achieve > 95% CO selectivity. While the reaction temperature had a considerable influence on the CPOM product H-2/CO ratio, the space velocity (at 850 degrees C) did not affect it to any significant extent. For the OSRM process, the H2O/CH4 ratio and the reaction temperature had a strong effect on the product H-2/CO ratio and the heat of the reaction; depending on the H2O/CH4 ratio and reaction temperature, the OSRM process could be operated in a mildly exothermic, thermoneutral or mildly endothermic mode. The CO2 conversion was very strongly affected by the reaction temperature in the OCRM process; reasonably high CO2 conversion ( > 40%) could only be obtained at high OCRM reaction temperatures ( > 850 degrees C). The exothermicity of the OCRM reaction was found to decrease with increasing reaction temperature. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: dry (CO2) reforming; high-temperature stable; methane; oxy-steam reforming; Partial oxidation; Steam reforming; Syngas

Energy-efficient syngas production through, catalytic oxy-methane reforming reactions - Choudhary, Tushar V.; Choudhary, Vasant R. (Angewandte Chemie-International Edition, 2008)
Keywords: fuels; heterogeneous catalysis; methane activation; Partial oxidation; Syngas

Carbon dioxide reforming of methane over ruthenium substituted strontium titanate perovskite catalysts - Gurav, Hanmant R.; Bobade, Richa; Das, Vineetha Lakshmi; Chilukuri, Satyanarayana V. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Strontium titanate (SrTiO3) doped with varying amounts of ruthenium (7.9, 15.6 and 31 wt%) have been prepared by the citrate gel synthesis method. Structural and textural characterizations reveal that at lower concentrations, a major part of Ru is incorporated in the lattice of SiTiO3. The content of surface Ru (outside lattice) increases with increasing amounts of the doped Ru. The surface Ru reduced at lower temperatures compared to Ru incorporated into the lattice. The reduction of the lattice substituted Ru occurs only at temperatures above the collapse of the perovskite structure. The catalyst sample with 7.9 wt% of Ru shows good conversions in the dry reforming of methane with CO2. The conversion of CO2 is in excess compared to methane under the studied reaction conditions. As a result, H-2/CO ratio of the product gases which should have been equivalent to unity is lower than the stoichiometric value. This ratio is particularly low when lower reaction temperatures (873-973 K) were used. Similar was the case when high space velocities were used. Low methane conversion and reverse water gas shift reaction are the causes for the low H-2/CO ratios.
Keywords: Carbon dioxide reforming; Catalysts; Citrate gel method; Doped catalysts; Dry reforming; Methane reforming; Perovskites; Reverse water gas shift; Ruthenium doped catalysts; Strontium titanate; Syngas

Dry reforming of methane in DBD plasma over Ni-based catalysts: influence of process conditions and support on performance and durability - Ray, Debjyoti; Nepak, Devadutta; Janampelli, Sagar; Goshal, Partha; Subrahmanyam, Ch (Energy Technology, 2019)
The conversion of greenhouse gases, H-2 and CO selectivity, H-2/CO ratio, and carbon formation in the dry reforming reaction over Ni-supported ZSM-5, Al2O3, and TiO2 are tested under thermal, plasma, and plasma-thermal conditions. It is observed that the dielectric nature, specific surface area, and acid-base properties of the support influence the performance during the DRM reaction. Typical results indicate that the best activity and syngas yield are achieved with 15Ni/Al2O3 under plasma conditions, possibly due to the high dielectric constant and surface area of Al2O3 and nanosize of Ni. In the thermal condition, the highest conversion of 73% and 68% for CH4 and CO2, respectively, is achieved over 15Ni/ZSM-5 at 500 degrees C. Plasma-assisted thermal conditions provide the highest conversion due to the activation of reactants and their partial conversion in the plasma zone before entering into the catalytic zone. The plasma-assisted thermocatalytic conversions of CH4 and CO2 reach the best values of 76% and 71%, respectively, on 15Ni/ZSM-5. Under the same conditions, 68% and 65% conversion of CH4 and CO2, respectively, is achieved with 15Ni/Al2O3 where the selectivity for H-2 and CO is 45% and 58%, respectively.
Keywords: DBD plasma; Dry reforming; reaction conditions; supported catalysts; Syngas

Metal-organic frameworks for enhanced hydrogen generation from syngas: a density functional theory approach - Gopalsamy, Karuppasamy; Singh, Chandrodai Pratap; Krishnamurty, Sailaja; BabaRao, Ravichandar (CHEMPLUSCHEM, 2024)
Keywords: carbon capture; H-2 separation; Metal organic; Porous coordination network (PCN-250); Syngas

Photocatalytic CO2 reduction to syngas using nickel phosphide-loaded CdS under visible light irradiation - Yadav, Poonam; Kumar, Santosh; Velankanni, Nandhakumar; Kuehne, Thomas D.; Gosavi, Suresh; Raghupathy, Ramya Kormath Madam; Bhosale, Reshma; Held, Georg; Shelke, Manjusha; Ogale, Satishchandra (Journal of Physics-Energy, 2024)
Photocatalytic CO2 reduction is a sustainable pathway to produce syngas (H-2 + CO), which is a key feedstock for the production of several important liquid fuels on the industrial scale. However, achieving an appropriate tunable ratio of H-2:CO in syngas for commercial purposes is a challenging task. In this work, we present a low-cost and non-noble metal, phosphide-based co-catalyst-Ni2P-loaded cadmium sulfide (CdS) photocatalyst system, for photocatalytic CO2 reduction. As a co-catalyst, Ni2P fosters an efficient charge separation of photoexcited charges generated in the CdS production of syngas. In total, 3 wt.% Ni2P/CdS exhibited exceptional performance of 50.6 mu mol g(-1) h(-1) in the CO evolution rate and 115 mu mol g(-1) h(-1) in the H-2 evolution rate, with a syngas composition varying from 2 to 4 in the H-2:CO ratio. Furthermore, first-principles density functional theory calculations were performed to study the surface energetics of the catalyst system and the results are found to be consistent with our experimental findings. Indeed, they establish that the composite favors CO2 photoreduction into syngas more efficiently than pure surfaces.
Keywords: CdS; CO2 reduction; Photocatalysis; Syngas; transition metal phosphides